2017
DOI: 10.1039/c7dt00217c
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric two-fold interpenetrated 3D zinc(ii) coordination networks as a catalytic platform: significant difference between water within the cage and trace water in transesterification

Abstract: Self-assembly of Zn(ClO) with 1,1,2,2-tetramethyl-1,2-di(pyridin-3-yl)disilane (L) as a bidentate N-donor gives rise to 3D coordination networks, [Zn(μ-OH)(L)](ClO)·5HO (1·5HO), of unique, 10-a srs net topology. An important feature is that two enantiomeric 3D frameworks, 4- and 4-[Zn(μ-OH)(L)](ClO)·5HO, are interpenetrated to form a racemic two-fold 3D network with cages occupied by two water molecules. Another structural characteristic is a C-symmetric planar Zn(μ-OH) 6-membered ring with tetrahedral Zn(ii) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Notable results were obtained in the heterogeneous catalytic conversion of phenyl acetate in the corresponding butyl ester (entry 15.2). Finally, Ok‐Sang Jung et al [44] . combined Zn(ClO 4 ) 2 and 1,1,2,2‐tetramethyl‐1,2‐di(pyridin‐3‐yl)disilane to produce a 3D‐structure exhibiting heterogeneous catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notable results were obtained in the heterogeneous catalytic conversion of phenyl acetate in the corresponding butyl ester (entry 15.2). Finally, Ok‐Sang Jung et al [44] . combined Zn(ClO 4 ) 2 and 1,1,2,2‐tetramethyl‐1,2‐di(pyridin‐3‐yl)disilane to produce a 3D‐structure exhibiting heterogeneous catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…In 2008 Cordeiro et al [21] efficiently used the layered hydroxide salt (LHS) [Zn 5 (OH) 8 (NO 3 ) 2 • 2H 2 O] as heterogeneous [44] catalysts for the esterification of lauric acid (and the transesterification of vegetable oils) with methanol and ethanol (entries 12.1-14.1). Based on PXRD and FTIR analyses of the recovered catalyst after the first run, they assumed replacement of the nitrate ion with laurate inside the crystalline lattice.…”
Section: Esterificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Iso-propanol could achieve the esterification of most PFCAs, with PFBA as an exception. Nevertheless, the responses of the peaks by iso-propanol were much lower compared with those generated by methanol and ethanol, probably due to the relatively lower esterification efficiency caused by the steric hindrance in the molecular structure of iso-propanol [29,30]. Therefore, it can be concluded that the PFCAs esters approach was only feasible for the derivatization of PFCAs with a longer carbon chain (>C6), but inadequate for short-chained PFCAs, such as PFBA and PFPeA.…”
Section: Screening Of Appropriate Derivative Methodsmentioning
confidence: 98%
“…Current trends in research on desirable metal-organic coordination species have prioritized efficient applications. [1][2][3][4][5][6][7][8][9][10][11][12] Among the various relevant factors therein, counteranions play significant roles in both the process of topology formation and the functions of various coordination systems such as catenanes, rotaxanes, macrocycles, cages, and infinite networks. [13][14][15] In particular, a momentous challenge for comprehensive molecular cage systems that include anions is to discover task-specific functions such as recognition, adsorption/desorption, molecular containers, ion exchangers, chemo-sensors, proton conductivity, drug delivery, and catalysis.…”
Section: Introductionmentioning
confidence: 99%